Social Mechanisms to Get People Outdoors: Bimodal Distribution of Interest in Nature? - Buckley, Ralf Christopher; Westaway, Diane; Brough, Paula (Frontiers in Public Health, 2016)
We report results from a post-program survey (n=930) of participants in a non-profit outdoor health program targeted principally at women with families in Australia’s metropolitan cities. We analyse communications, motivations, experiences, satisfaction and intentions. The program involves three months’ outdoor training in scenic locations, culminating in a single-day event. Training includes social opportunities and peer-group support. Event entry is in teams, and includes charitable fundraising and personal challenges. Drop-out rates are very low, and repeat sign-up high. There are 2000-3000 places per event, and the most recent sold out in <24 hr. We propose that for urban residents of developed nations, individual interest in exposure to nature may be bimodal rather than unimodal. Programs of this type target individuals most likely to shift from low-interest to high-interest mode, using a set of social levers to change attitudes and behaviours. This contrasts with most public outdoor health programs, which assume a unimodal distribution and aim for small lifestyle changes at population scale. We suggest that the bimodal hypothesis is relevant to the sociocultural context of psychosocial interventions in a public health context, and merits direct testing.